Is the date of birth an advantage/ally to excel in handball? - Sánchez-Rodriguez, C.; Grande, I.; Sampedro, J.; Rivilla-Garcia, J. (Journal of Human Sport & Exercise, 2013)
The relative Age Effect (RAE) has been analyzed in a population of Spanish international handball players (n=161) divided into four different levels: Senior, Junior, Juvenile and Promising Talents. The variables registered were quarter, half year and year of birth using the initial information of their date of birth. The data were collected from the Royal Spanish Handball Federation on-line data base. The statistical method used was the x2 and the minimum level of significance was set at p<0.05. The total results on distribution by quarter show a significant difference (x2= 21.68; p<0.01) with a greater frequency of players born in the first quarter (40.37%) compared to those born in the second (22.36%), third (16.15%) and fourth quarter (21.12%). The total results on the distribution of birth date by half year show a significant difference (x2= 10.44; p<0.01) with a greater frequency of players born in the first half of the year (62.73%). With regard to the rate of births registered in an even numbered or odd numbered year there are significant differences when the rates for an even numbered year (64.60%) and an odd numbered year (35.40%) are compared with those of the general population (x2= 13.72; p<0.001). Based on the data collected and analyzed it can be concluded that there is a RAE in the basic categories of the Spanish national men`s handball teams according to quarter, half year and year of birth (even or odd numbered), but there exists little knowledge about the causes and consequence which may be produced by, or derive from, this effect.